Sarawak Hemic Peat Consolidation Settlement and Shear Strength Behaviour - Sa‘don, N.M.; Abdul Karim, A. R.; Ahamad, Z.; Mariappan, A. (2016)
Peat layer in Sarawak alone represents 13 percent or about 1.66 million hectares of Sarawak‘s total land area. They are mostly in low-lying areas; with in some areas, peat exceeding 10 m in depth. During past few decades, the demands of urbanisation resulted in the expansion of land development into swamp and deep peat areas. Thus, proper understanding, management and construction practices should be emphasized on peat to overcome consequential occurrence of ground subsidence problems. The objectives of this study are to investigate the consolidation settlement parameters and shear strength behaviour of hemic peat in Sarawak. The samples were taken from Matang, Batu Kawa, and Kota Samarahan, Sarawak. The initial characteristic tests consist of the degree of humidification, loss on ignition, Atterberg limit, particle density; moisture content and pH value. The results recorded high moisture content and organic content for Sarawak hemic peat. The value of Compression Index, Cc, determined from the oedometer test for hemic peat is in the range of 1.13 to 3.20 and compression ratio, Cc/1+eo is classified as very compressible (> 0.20) for all three locations; Matang, Batu Kawa and Kota Samarahan,. From the direct shear box test, the cohesion, c′ values are in the range of 8.0-18.0 kPa and angle of internal friction φ′ in the range of 24o- 37o.